2007
DOI: 10.1111/j.1524-475x.2007.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro binding of matrix metalloproteinase‐2 (MMP‐2), MMP‐9, and bacterial collagenase on collagenous wound dressings

Abstract: Chronic wounds are characterized by failure in wound-healing response and a delay in healing or nonclosure of the wounds. This results in a high effort in clinical treatment and/or home care. A major difference between acute wounds and chronic wounds is the imbalance of proteinase inhibitors and proteinase activity that regulates the degradation and regeneration of the extracellular matrix proteins. Collagen and collagen/oxidized regenerated cellulose dressings act as a competitive substrate for matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Recently, it has been shown that bacterial collagenase (as well as human MMPs) can be bound to collagen or oxidized regenerated cellulose/collagen sponge. 87 This, together with the notion that components of the matrix degraded by bacterial collagenase have stimulatory effects on cells within the wound bed—epithelial, endothelial, inflammatory cells, and fibroblasts—suggest that matrix-based wound dressings may serve to deliver the enzyme into a wound bed.…”
Section: Chronic Wound Carementioning
confidence: 99%
“…Recently, it has been shown that bacterial collagenase (as well as human MMPs) can be bound to collagen or oxidized regenerated cellulose/collagen sponge. 87 This, together with the notion that components of the matrix degraded by bacterial collagenase have stimulatory effects on cells within the wound bed—epithelial, endothelial, inflammatory cells, and fibroblasts—suggest that matrix-based wound dressings may serve to deliver the enzyme into a wound bed.…”
Section: Chronic Wound Carementioning
confidence: 99%
“…38 Likewise, the incorporation of collagen-I substrates into wound dressings has been shown to effectively sequester not only the mammalian gelatinases MMP-2 and MMP-9 but also Clostridium histolyticum bacterial collagenase. 39 Photodynamic therapy. Photodynamic therapy (PDT) is the application of a photoactive dye followed by irradiation, which leads to cell death in the presence of oxygen.…”
Section: Bacterial Proteases As Diagnostic Markers In Chronic Woundsmentioning
confidence: 99%
“…The enzyme bound to the collagen fibers. However, because of the dense matrix structure, the reduced surface area, and limited binding sites, the binding of enzyme onto minirods was delayed and thus less pronounced in comparison with porous wound dressings [28]. …”
Section: Discussionmentioning
confidence: 99%